The Identification Problem for Multiple Equation Systems with Moving Average Errors - Hannan, E. J. (Econometrica, 1971)
where y(t) and x(t) are vectors of G components, z(t) has K components, B is a G x G matrix, and F is a G x K matrix.' The components of z(t) are predetermined at time t and the vector x(t) is not serially correlated, so that (among other requirements) we have